Analysis of predictive factors for perforated appendicitis in children. Issue 6 (8th June 2020) - Miyauchi, Harunori; Okata, Yuichi; Hatakeyama, Tadashi; Nakatani, Taichi; Nakai, Yumiko; Bitoh, Yuko
Abstract: Background: The aim of this research was to investigate the diagnostic value of objective factors present at admission for identifying predictive markers of perforated appendicitis in children. Methods: We performed a retrospective case review of 319 children aged ≤15 years who underwent treatment for acute appendicitis at our institution over a 6‐year period from January 2011 to December 2016. Univariate and multivariate analyses were performed to identify risk factors for perforation of acute appendicitis in children. Results: In the 6‐year period, 319 patients underwent treatment for acute appendicitis, of whom 72 (22.6%) had perforated appendicitis. Multivariate analysis revealed five independent factors predicting perforated appendicitis at admission: longer symptom duration (≥2 days), fever (axillary temperature ≥38.0 °C), elevated C‐reactive protein level (≥3.46 mg/dL), appendiceal fecalith on imaging, and ascites on imaging. Among patients with all five risk factors, 93.3% had perforated appendicitis. None of the patients without any of these factors had a perforated appendicitis. Conclusions: Longer symptom duration (≥2 days), fever (axillary temperature ≥38.0 °C), elevated C‐reactive protein level, and the presence of appendiceal fecalith and ascites on imaging are independent and objective factors predicting perforated appendicitis at admission. These risk factors have the potential to be helpful as an ancillary index for physicians determining the severity of appendicitis.